Adventitious carbon breaks symmetry in oxide contact electrification - Galien Grosjean; Markus Ostermann; Markus Sauer; Michael Hahn; Christian M. Pichler; Florian Fahrnberger; Felix Pertl; Daniel M. Balazs; Mason M. Link; Seong H. Kim; Devin L. Schrader; Adriana Blanco; et al. (Nature, 2026)
Abstract Insulating oxides are among the most abundant solid materials in the universe 1–3 . Of the many ways in which they influence natural phenomena, perhaps the most consequential is their capacity to transfer electrical charge during contact 4–10 —which occurs even between samples of the same oxide—yet the symmetry-breaking parameter that causes this remains unidentified 11,12 . Here we show that adventitious carbonaceous molecules adsorbed from the environment are the symmetry-breaking factor in same-material oxide contact electrification (CE). We use acoustic levitation to measure charge exchange between a sphere and a plate composed of identical amorphous silicon dioxide (SiO 2 ). Although charging polarity is random for co-prepared samples, we control it with baking or plasma treatment. Observing the charge-exchange relaxation afterwards, we see dynamics over a timescale of hours and connect this directly to the presence of adventitious carbon with time-of-flight mass spectrometry, low-energy ion scattering and infrared spectroscopy. Going further, we confirm that adventitious carbon can even determine charge exchange among different oxides. Our results identify the symmetry-breaking parameter that causes insulating oxides to exchange charge in settings ranging from desert sands 4 to volcanic plumes 5,6 , while simultaneously highlighting an overlooked factor in CE more broadly.